(untitled) (Fiep Bulletin - online, 2014)
Between the healthful behaviors, the practical one of physical activity has been widely stimulated for the world-wide programs of promotion of the health in view of its physical and psicossociais benefits. The objective of this study was to analyze as the necessities and social value of the physical activities, in the perception of the aged one, if they place for the practical ones of the health in general way and where bases these if define when taking the aged one as its object from the Theory of the Social Representations. 70 individuals had been investigated, of both the sexes, with age varying of 50 the 78 years, inhabitants of the city of Natal (RN), Brazil. The collection of data carried through an open question was inquired by the Analysis of Content of Bardin and by software Alceste 4,5. The analysis of the data made possible the construction of the categories: Change of Attitude; Autonomy; Happiness; Style of Life; Quality of Life, in allowing to conclude that a dichotomy exists physical activity and health in the aging process. Thus, to have better physical and motor aptitude, more corporal health and more efficient answers meant much more of what not having illnesses, or more disposal to make the activities.